The incidence of eurocommunism in the policy of the brazilian communist party and the diffusion of Gramsci’s work - Del Roio, Marcos [UNESP] (FapUNIFESP (SciELO), 2023)
The intention of this article is to show how the incidence of Eurocommunism in the Brazilian Communist Party and the dissemination of Gramsci’s work are part of the same process, and how Eurocommunism was a failed effort to update the strategic orientation of the communist movement. The emphasis is on the political and cultural action of intellectuals, so it is also a brief page on the history of Brazilian intellectuals, without centrally addressing the uses of Gramsci’s theoretical categories. It is not part of this exhibition the impact of Gramsci’s thought on the left that would later converge in the creation of PT (Brazilian Workers’ Party): the Catholic left and other Marxist variants. Neither are some precursor productions presented at the academy. Available documentation can be found in books, newspapers, and magazines. This path served to spread Gramsci’s name in Brazil during the political struggle, but from the theoretical-scientific point of view, the gains were not many, despite the promising essay that was outlined.
A INCIDÊNCIA DO EUROCOMUNISMO NA POLÍTICA DO PARTIDO COMUNISTA BRASILEIRO E A DIFUSÃO DA OBRA DE GRAMSCI
Keywords: Brazilian Communist Party; Eurocommunism; Eurocomunismo; Gramsci; Italian Communist Party; Partido Comunista Brasileiro; Partido Comunista Italiano